Comparative Analysis of the Equivital EQ02 Lifemonitor with Holter Ambulatory ECG Device for Continuous Measurement of ECG, Heart Rate, and Heart Rate Variability: A Validation Study for Precision and Accuracy - Akintola, Abimbola A.; van de Pol, Vera; Bimmel, Daniel; Maan, Arie C.; van Heemst, Diana (Frontiers in Physiology, 2016)
Background: The Equivital (EQ02) is a multi-parameter telemetric device offering both real-time and/or retrospective, synchronized monitoring of ECG, HR and HRV, respiration, activity and temperature. Unlike the Holter, which is the gold standard for continuous ECG measurement, EQO2 continuously monitors ECG via electrodes interwoven in the textile of a wearable belt. Objective: To compare EQ02 with the Holter for continuous home measurement of ECG, heart rate (HR) and heart rate variability (HRV). Methods: Eighteen healthy participants wore, simultaneously for 24 hours, the Holter and EQ02 monitors. Per participant, averaged HR and HRV per 5 minutes from the two devices were compared using Pearson correlation, paired T-test and Blant-Altman analyses. Accuracy and precision metrics included mean absolute relative difference (MARD). Results: Artefact content of EQ02 data varied widely between (range 1.93% to 56.45%) and within (range 0.75% to 99.61%) participants. Comparing the EQ02 to the Holter, the Pearson correlations were respectively 0.724, 0.955 and 0.997 for datasets containing all data and data with <50% or <20% artefacts respectively. For datasets containing respectively all data, data with <50% or <20% artefacts, bias estimated by Bland-Altman analysis was -2.8, -1.0 and -0.8 beats per minute and 24h MARD was 7.08, 3.01 and 1.5. After selecting a three- hour stretch of data containing 1.15% artefacts, Pearson correlation was 0.786 for HRV measured as standard deviation of NN intervals (SDNN). Conclusions: Although the EQ02 can accurately measure ECG and HRV, its accuracy and precision is highly dependent on artefact content. This is a serious limitation for clinical use in individual patients. However, the advantages of the EQ02 (ability to simultaneously monitor several physiologic parameters) may outweigh its disadvantages (higher artefact load) for research purposes and/ or for home monitoring in larger groups of study participants. Further studies can be aimed at minimizing the artefacts.